Efficient Access to Isoquinolines via Rhodium-Catalyzed Oxidative Annulation of Pyridyl C–H Bonds Directed by Carbonyl with Internal Alkynes - Shi, Lijun; Wen, Mingshan; Li, Fuwei (Synthesis, 2020)
An efficient synthesis of amino-substituted isoquinolines via Rh(III)-catalyzed oxidative [2+2+2] annulation of pyridines with alkynes has been developed, which is cooperatively enabled by a directing carbonyl and steric hindrance adjacent to the amino group of the pyridine, via a six-membered rhodacyclic intermediate without coordination with the pyridinic nitrogen. The establishment of this C–H activation strategy also paves the way for other oxidative transformations of heterocyclic C–H bonds.
Keywords: rhodium; oxidative [2+2+2] annulation; C–H activation; isoquinolines; cooperative catalysis